Associations Between Physical and Relational Forms of Peer Aggression and Victimization and Risk for Substance Use Among Elementary School-Age Youths. Issue 1 (2nd January 2016) - Fite, Paula J.; Gabrielli, Joy; Cooley, John L.; Rubens, Sonia L.; Pederson, Casey A.; Vernberg, Eric M.
ABSTRACT: This study examined associations between physical and relational forms of aggression and victimization and risk for willingness to engage in substance use and actual use in a sample of 231 (50% male) second- through fourth-grade students (mean age = 8.3 years). Physical aggression was more strongly associated with risk for substance use outcomes than physical victimization. Neither relational aggression nor victimization were linked to risk for substance use. Specifically targeting physical aggression for the prevention of early substance use among elementary school-age youths appears to be warranted.